Effect of low-carbon paraffinic fuels on spray evolution under typical operating conditions for piston-engine aircrafts - Corral-Gómez, Lis; Armas, Octavio; Moya-Fernández, Francisco; A. Soriano, José; Martos, Francisco J.; Nogueira, José (Frontiers in Mechanical Engineering, 2025)
The evolution of the main macroscopic parameters that characterize spray formation for three different fuels is studied by means of the Schlieren visualization technique. The annalized fuels comprise a fossil diesel fuel, used as reference, and two neat low carbon liquid 100% paraffinic fuels: a gas-to-liquid (GtL) and a hydrotreated vegetable oil (HVO). Additionally, the paper exposes the behavior of fuels autoignition for different injection pressures and start of energizing (SoE), for prescribed thermodynamic variables inside the engine cylinder. The experimental results obtained at the beginning of the injection process are compared with results from known models of penetration and cone angle of the fuel spray under non-evaporative conditions. These conditions are chosen to match those of the diesel engines used in surveillance light aircraft such as small helicopters. This work presents two important novelties: (i) the application of an automatic image analysis procedure (previously published) to the fuel injection process and (ii) the comparison of different fuels, regarding their effect on the injection process and the start of combustion. This is done under complete replacement of fossil fuel by two 100% paraffinic fuels. The most important results are the following: i) Compared to GtL and Diesel fuels, the HVO fuel has shorter ignition delay. This result could be attributed to its higher cetane number. ii) However, in most of the tested cases, in addition to a slightly longer spray penetration of the HVO fuel, its cone angle is also slightly wider than that of the other two fuels. This result would be collaborating in the development of a wider spray surface during the evolution of the spray lift off and beyond. This leads to a better air entrainment, and, in consequence, to produce an additional shortening of the ignition delay compared to the other two fuels. These findings would facilitate the fine tuning of modern engine technology for a progressive introduction of mentioned low carbon fuels in light aircraft such as unmanned helicopters for surveillance.